2022
DOI: 10.3389/fnins.2022.880105
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Association Between Lead Pollution and Risk of Alzheimer’s Disease by Integrating Multigenomics

Abstract: Alzheimer’s disease (AD) is a life-threatening neurodegenerative disease of the elderly. In recent observations, exposure to heavy metals environmental may increase the risk of AD. However, there are few studies on the causal relationship between heavy metal exposure and AD. In this study, we integrated two large-scale summaries of AD genome-wide association study (GWAS) datasets and a blood lead level GWAS dataset and performed the two-sample Mendelian randomization analysis to assess the causality of blood l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Pb interacts with Aβ [ 31 ] and increases Aβ production [ 45 , 164 ] and aggregation [ 31 ], increases tau hyperphosphorylation [ 165 ], compromises the BBB [ 36 ], induces epigenetic modifications by altering the expression of AD-related genes [ 166 , 167 ], disrupts intracellular cation homeostasis by interfering with Ca homeostasis and replacing Zn ions in Zn enzymes [ 168 ], and induces oxidative stress [ 169 ]. In human studies, there was a decrease or no difference in the Pb levels between the AD patients and control subjects ( Table 1 ), whereas a recent MR study found that higher blood Pb levels were a risk factor for AD [ 170 ].…”
Section: Heavy Metals In Alzheimer’s Diseasementioning
confidence: 99%
“…Pb interacts with Aβ [ 31 ] and increases Aβ production [ 45 , 164 ] and aggregation [ 31 ], increases tau hyperphosphorylation [ 165 ], compromises the BBB [ 36 ], induces epigenetic modifications by altering the expression of AD-related genes [ 166 , 167 ], disrupts intracellular cation homeostasis by interfering with Ca homeostasis and replacing Zn ions in Zn enzymes [ 168 ], and induces oxidative stress [ 169 ]. In human studies, there was a decrease or no difference in the Pb levels between the AD patients and control subjects ( Table 1 ), whereas a recent MR study found that higher blood Pb levels were a risk factor for AD [ 170 ].…”
Section: Heavy Metals In Alzheimer’s Diseasementioning
confidence: 99%